The Role of Natural Halogens in Global Tropospheric Ozone Chemistry and Budget Under Different 21st Century Climate Scenarios. Issue 20 (19th October 2021) - Badia, Alba; Iglesias‐Suarez, Fernando; Fernandez, Rafael P.; Cuevas, Carlos A.; Kinnison, Douglas E.; Lamarque, Jean‐Francois; Griffiths, Paul T.; Tarasick, David W.; Liu, Jane; Saiz‐Lopez, Alfonso
Abstract: Tropospheric ozone ( O 3 ) is an important greenhouse gas and a surface pollutant. The future evolution of O 3 abundances and chemical processing are uncertain due to a changing climate, socioeconomic developments, and missing chemistry in global models. Here, we use an Earth System Model with natural halogen chemistry to investigate the changes in the O 3 budget over the 21st century following Representative Concentration Pathway (RCP)6.0 and RCP8.5 climate scenarios. Our results indicate that the global tropospheric O 3 net chemical change (NCC, chemical gross production minus destruction) will decrease ∼ 50 %, notwithstanding increasing or decreasing trends in ozone production and loss. However, a wide range of surface NCC variations (from −60 % to 150 % ) are projected over polluted regions with stringent abatements in O 3 precursor emissions. Water vapor and iodine are found to be key drivers of future tropospheric O 3 destruction, while the largest changes in O 3 production are determined by the future evolution of peroxy radicals. We show that natural halogens, currently not considered in climate models, significantly impact on the present‐day and future global O 3 burden reducing ∼ 30–35 Tg (11–15 % ) of tropospheric ozone throughout the 21st century regardless of the RCP scenario considered. This highlights the importance of including natural halogen chemistry in climate model projections of future tropospheric ozone. Key Points: Water vapor and iodine are key drivers of future tropospheric ozone destruction Natural halogens reduce 30–35 Tg of tropospheric ozone burden throughout the 21st century regardless of the Representative Concentration Pathway scenario considered Enhanced halogen‐driven surface ozone loss will determine the effectiveness of future policies on air quality